Raiding the Superhero Wardrobe: A Review of The Superhero Costume – Identity and Disguise in Fact and Fiction: The Superhero Costume – Identity and Disguise in Fact and Fiction, B. Brownie and D. Graydon, Bloomsbury Academic, 192 pages, 2016, 15 b/w images, ISBN: 978-1472595904. Issue 1 (17th January 2018) - Gröppel-Wegener, Alke
Abstract : This review provides a costume designer's reading of The Superhero Costume – Identity and Disguise in Fact and Fiction by Barbara Brownie and Danny Graydon (Bloomsbury, 2016). This book explores the superhero costume within comics, films and its translation into real life, and shows how difficult it is to stitch the line between symbolism and practicality, spectacle and realism, and ultimately between fiction and fact. While there remains some unevenness in how the gender of superheroes makes a difference to the costume and there is a lack of a useful conclusion as far as academic books go, this book discusses a lot of issues that could (and should) inform the designs within a superhero's wardrobe.